Understanding the effects of Twitter-based crisis communications strategies on brand reputation - Boman, Courtney (Kansas State University, 2017)
The Situational Crisis Communications Theory (SCCT) states that what organizations say to various publics during a crisis should influence the extent of the reputational and financial damage a crisis can inflict on the organization's image. Past research has focused on distinguishing types of crises and what crisis-communication strategies should be used with traditional media. Research exists, but looks at social media and its effects on brand reputation during a crisis via case studies or is an experimental design focused on the information source. There is a lack of controlled experimental studies that investigate the role of social media in crisis-communications strategies. Guided by Coombs’ Situational Crisis Communications Theory, this controlled experimental design employed a 2x2 factorial design. The independent variables were (a) type of crisis (preventable, accidental) and (b) type of response (rebuild, diminish) used on Twitter. The dependent variable was organizational brand reputation. Survey participants were recruited through a paid Qualtrics panel who were millennials that live in Midwestern states. Specific research questions were RQ 1: Will all participants begin with the same pre-test score; RQ 2: Is there a time effect on brand reputation; RQ 3: Does an accidental crisis change brand reputation; RQ 4: Does a preventable crisis change brand reputation; RQ 5: Does brand reputation change vary by crisis type? Based on findings in previous research, hypotheses developed were: H1: Brand reputation will be consistent from pre-brand to post-brand test for matched crisis responses; H2: Post-brand tests for unmatched accidental responses will be consistent with or better than pre-brand tests; H3: Post-brand tests for unmatched preventable responses will be lower than pre-brand tests. The findings from this study give insight to how SCCT translates to Twitter. In this study, matched responses did not maintain reputation as the SCCT literature suggests. In addition, the accidental unmatched condition did not perform better than the matched condition. However, unmatched preventable did have a bigger decline in brand reputation than matched, suggesting it could be better to have no response than the wrong response in some situations. This study confirms the need for practitioners to understand the crisis type prior to responding and understand the role of social media in communication. Throughout the study, it was found that using an unmatched response could cause a decrease in brand reputation. This is especially true when using a low-attribution response for a high-attribution situation, as the response will fall short of what the crisis requires.
Keywords: Crisis communication; Situational Crisis Communication Theory; Social media; Twitter; Brand reputation